An investigation into the use of smectitic clay soil for the containment and treatment of petrochemical waste - Huntsman, Philippa Rose (Department of Geological Sciences, 2016)
The manufacture, transport, use and disposal of organic chemicals may result in the release of significant quantities of organic substances into soil, from which they are subject to possible transport into underlying groundwater. Many of these organic chemicals are potentially toxic (Wilson et al., 1981). Information is required concerning the chemical and physical behaviour of organic chemicals in the soil environment in order to implement measures that will protect groundwater but also permit reasonable usage of soil for waste containment. This study deals with the interactions of a smectitic clay soil of the Rensburg form and two petrochemical wastes, which were sampled from storage dams, adjacent to a petrochemical plant at Secunda, South Africa. There is growing interest at the plant in utilizing soil for cost-effective waste containment and treatment. The objectives of this study were twofold: firstly, to determine the permeability of the Rensburg soil with respect to the two waste liquids (BPlO- aqueous and phenolic, and BP2- non-aqueous); and, secondly, to investigate the sorptive capacity of the clay fraction of the soil for two common groundwater contaminants, benzene and phenol, in the context of the potential for using treated clays for decontaminating BP10 and other organic wastes. The Rensburg soil was compared with a commercial bentonite for containing and treating petrochemical waste.